Earth. (Princeton, NJ : Two Can, 2000)
Includes a color-illustrated book and a CD-ROM for Windows or Macintosh that work together to describe many facets of earth science and biology.
Includes index.
5.0.
5.0
3-6
System requirements for computer disc: 486DX2/66MHz; 8MB RAM; WIN 3.1/WIN 3.11/WIN 95/WIN 98; 256-col. display; sd. card.
System requirements for computer disc: MAC 68020/PowerPC; 16MB/24MB RAM; System 7.0+.
Keywords: Earth sciences -- Juvenile literature; Earth sciences; Earth sciences